DEVELOPING MATHEMATICS LEARNING MATERIALS ABOUT FLOW RATE USING INTERACTIVE POWERPOINT FOR FIFTH GRADE STUDENTS - Putri Zudhah Ferryka; Sri Suwartini (Indonesian Journal of Elementary Teachers Education, 2020)
The purpose of this study was to examine the effectiveness of mathematics learning application media for the fifth-grade elementary school students about the flow rate. The research was designed to develop learning material using interactive PowerPoint media. The study was conducted at Barenglor 4 Elementary School. This study used the Research and Development (RD) method by employing four procedures development which include: (a) exploration, (b) the development of the draft/prototype, (c) test try products and revisions, and (d) final validation. The research subjects were fifth-grade students at Barenglor 4 Elementary School. A total of 48 students were separated into two groups. There were 24 students in the experimental group and 24 students in the control group. The independent sample t-test was used to analyze the data with a significance level of 0.05. The researcher used expert judgment both academicians and practitioners. The results of the study showed that the learning tools were reviewed by the experts of material, media, and evaluation about the aspects of syllabi, lesson plans, instructional media, and assessing for learning outcomes categorized as "Very Good". The application of learning tools, in general, can be reached with the "Very Good" category. Then, the difference in the final results between the control class and the experimental class after using a thematic-integrative learning tool with p0.05.Keywords: mathematics learning; flow rate; interactive powerpoint.